KEDUDUKAN HUKUM ISLAM DALAM SISTEM HUKUM NASIONAL DI INDONESIA - Tomi Saladin (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2021)
Artikel info:  Received: Agustus 2021Accepted: Agustus 2021Available online: Desember 2021 ABSTRAC Looking for the position of Islamic law in the national legal system is clear, where Islamic law as contained in the government's legal politics in the GBHN stipulated by the MPR Number IV/MPR/1999 explains that the policy direction of legal development recognizes and respects religious law (including Islamic law) in managing the system. Comprehensive and integrated national law, and efforts are made so that all laws and regulations do not conflict with the morals of religions (including Islamic morals). Islamic law in the development of national law has two forms, 1) functioning of Islamic law as a positive law that applies only to Muslims. 2) functioning of Islamic law through the expression of values or principles of Islamic law which will apply not only to Muslims but also to all citizens. Islamic law in the perspective of positive Indonesian law can be classified into three groups, namely: (1) positive laws that are in line with Islamic law, such as family law and most civil laws, (2) positive laws that do not conflict with Islamic law. although not exactly the same as Islamic law, such as the law on murder and robbery, (3) positive laws that are contrary to Islamic law, such as the law on sexual relations without marriage, liquor and gambling where the perpetrators are punished only if they damage or disturb people other.This type of research is library research (library research), in the sense that all data sources come from written materials in the form of books, documents, magazines and texts that are related to the topic of discussion through a review of various literature related to research which includes primary, secondary data. , dantertier. The data collected, read.The result of this research is the development of law, so Islamic law, apart from being a legal norm, can be transformed into positive law in the national legal system. Islam and the Islamic Law system will always be the selectors of the national legislation process, because philosophically, juridically and sociologically the power of Islam is a reflection of Indonesia's future development. The reality of the plurality of the Indonesian nation will be a consideration in national legislation efforts, so that Islamic values will be more easily absorbed in the national legal system. Keywords: Islamic Law, Positive Law, and National Legal System.  ABSTRAKMencari posisi hukum Islam dalam sistem hukum nasional telah jelas, dimana hukum Islam sebagaimana termaktub dalam politik hukum pemerintan dalam GBHN yang ditetapkan MPR Nomor IV/MPR/1999 menjelaskan bahwa arah kebijakan pembangunan hukum mengakui dan menghormati hukum agama (termasuk hukum Islam) dalam menata sistem hukum nasional yang menyeluruh dan terpadu, dan diupayakan agar segala peraturan perundang-undangan tidak bertentangan dengan moral agama-agama (termasuk moral Islam). Hukum Islam dalam pembangunan hukum nasional mempunyai dua bentuk, 1) mengfungsikan hukum Islam sebagai hukum positif yang berlaku hanya bagi pemeluk Islam saja. 2) mengfungsikan hukum Islam melalui ekspresi nilai-nilai atau prinsip-prinsip hukum Islam yang akan berlaku tidak hanya bagi kaum muslim tetapi juga bagi semua warga negara. Hukum Islam dalam perspektif hukum positif Indonesia dapat diklasifikasikan ke dalam tiga kelompok yaitu: (1) hukum-hukum positif  yang sejalan dengan hukum Islam, seperti hukum keluarga dan sebagian besar hukum perdata, (2) hukum-hukum positif yang tidak bertentangan dengan hukum Islam meski tidak sama persis dengan hukum Islam, seperti hukum tentang pembunuhan dan perampokan, (3) hukum-hukum positif yang bertentangan dengan hukum Islam, seperti hukum tentang hubungan seksual tanpa nikah, minuman keras dan perjudian yang pelakunya dikenakan hukuman hanya jika merusak atau mengganggu orang lain.Jenis penelitian ini adalah penelitian kepustakaan (library research), dalam artian semua sumber data berasal dari bahan-bahan tertulis berupa buku, dokumen, majallah dan naskah yang ada kaitannya dengan topic pembahasan melalui penelaahan berbagai literatur yang berhubungan dengan penelitian yang mencakup data primer, sekunder, dantertier. Data-data yang dikumpulkan, dibaca.Hasil penelitian ini yaitu pembangunan hukum, maka hukum Islam selain sebagai norma hukum yang dapat ditranformasikan menjadi hukum positif dalam sistem hukum nasional. Islam dan sistem Hukum Islam akan selalu menjadi penyeleksi proses legislasi nasional, karena secara filosofis, yuridis dan sosiologis kekuatan Islam menjadi cermin pembangunan Indonesia kedepan. Kenyataan pluralitas bangsa Indonesia akan menjadi pertimbangan dalam upaya legislasi nasional, sehingga nilai-nilai Islam akan lebih mudah terserap dalam sistem hukum nasional. Kata kunci: Hukum Islam, Hukum Positif, dan Sistem Hukum Nasional.